Antennal lobe organization and pheromone usage in bombycid moths - Namiki, Shigehiro (The Royal Society, 2014)
We investigated the neuroanatomy of the macroglomerular complex (MGC), which is involved in sex pheromone processing, in five species in the subfamily Bombycinae, including Ernolatia moorei, Trilocha varians, Rondotia menciana, Bombyx mandarina and Bombyx mori. The glomerulus located at the dorsal-most part of the olfactory centre shows the largest volume in moth species examined to date. Such normal glomerular organization has been observed in E. moorei and T. varians, which use a two-component mixture and includes the compound bombykal as a mating signal. By contrast, the other three species, which use another component as a single attractant, exhibited a modified arrangement of the MGC. This correlation between pheromone usage and neural organization may be useful for understanding the process of speciation.